Hahn Sequence Space of Modals. (9th November 2014) - Balasubramanian, T.; Zion Chella Ruth, S.
Abstract : The history of modal intervals goes back to the very first publications on the topic of interval calculus. The modal interval analysis is used in Computer graphics and Computer Aided Design (CAD), namely, the computation of narrow bounds on Bezier and B -Spline curves. Since modal intervals are used in many fields, we introduce a new sequence space h(gI) called the Hahn sequence space of modal intervals. We have given some new definitions and theorems. Some inclusion relation and some topological properties of this space are investigated. Also dual spaces of this space are computed.